Analysis of Factors Affecting Low Coverage of Exclusive Breast Feeding - Reni Mareta; Robiul Fitri Masyitoh (Media Keperawatan Indonesia, 2018)
Food is a major factor supporting growth and development for every living creature. The quantity and composition of the food consumed is tailored to the needs of each individual. Babies have different food compositions. According to WHO the best food for babies is given breast milk as soon as the baby is born until the first 6 months and continued until the age of 2 years. This condition can not be achieved if coverage of ASI in each region is still less. One of the areas whose exclusive coverage is still low is Magelang City. Data from the health profile of the Magelang City Health Office in 2008 mentioned that in Magelang city there was a percentage of infants who got an exclusive ation of 0.32 percent. Looking at the phenomenon, researchers are interested to know the factors causing the low coverage of exclusive breastfeeding in the city of Magelang. This research is located in the working area of North Magelang Health Center. The model of this research is by observational analytic with cross sectional study design design with quantitative approach. Selection of sample by purposive sampling method with 30 sample people. This study uses questionnaires that we will share to samples that have children maximum 2 years old. The questionnaire contains questions about breastfeeding. From the results of the questionnaire will then be analyzed to determine the factors causing the low coverage of exclusive breastfeeding in the city of Magelang. The results of this study indicate there are several factors that affect the exclusive ation: among others: maternal age, level of education and mother's work. It is expected that the results of this study could be as input for the relevant agencies in this case is the Health Department to make appropriate policies to increase exclusive ASI coverage.